2017
DOI: 10.5897/ijnm2017.0266
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Seeking Behaviour on Neonatal Danger Signs among Mothers in Tenta District, Northeast Ethiopia: Community based cross- sectional study.

Abstract: Health care seeking behaviour is any action undertaken by individuals who perceive to have a health problem or to be ill for finding an appropriate remedy. It involves recognition of symptoms, perceived nature of illness, followed initially by appropriate home care and monitoring. In Ethiopia, little is known about mother's health care seeking behaviour on neonatal danger signs. Therefore, this study assessed the health care seeking behaviour on neonatal danger signs among mothers in Tenta district, Northeast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 13 publications
5
11
1
Order By: Relevance
“…This positive association explains the ANC visits' role in strengthening caregivers' knowledge and awareness regarding neonatal health and the availability of newborn healthcare services in health facilities [ 28 ]. Moreover, women who gave birth at a facility had three times higher odds of care-seeking from trained providers compared to those who gave birth at home, and the finding corroborated with other studies [ 2 , 7 , 18 ]. Giving birth at health institutions probably facilitated postnatal counseling leading to increased awareness of neonatal danger signs and seeking healthcare from skilled providers.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This positive association explains the ANC visits' role in strengthening caregivers' knowledge and awareness regarding neonatal health and the availability of newborn healthcare services in health facilities [ 28 ]. Moreover, women who gave birth at a facility had three times higher odds of care-seeking from trained providers compared to those who gave birth at home, and the finding corroborated with other studies [ 2 , 7 , 18 ]. Giving birth at health institutions probably facilitated postnatal counseling leading to increased awareness of neonatal danger signs and seeking healthcare from skilled providers.…”
Section: Discussionsupporting
confidence: 87%
“…Studies also reported prompt identification of danger signs and perceived quality of care for using skilled healthcare providers as determinants [ 19 , 20 ]. Furthermore, social factors such as autonomy of decision-making and accessibility to health facilities may also influence seeking skilled-care for sick neonates [ 18 , 20 ]. While a strengthened health system, with essential services and human resources, is needed to address the problem, recognizing illness and caregivers’ decision to reach the skilled healthcare providers are critical to reducing mortality.…”
Section: Introductionmentioning
confidence: 99%
“…In this study only 60.5% of mothers whom their baby developed danger-sign sought health care from health facility immediately. This finding was higher than study done in four regions of Ethiopia (1/3rd) and Tenta district (41.3%) women sought medical care for NDSs [27, 28]. The possible reason for this might be due to the variations in time, study setting, study population and cultural variations in which studies in four regions of Ethiopia and Tenta district were conducted in 2014 and 2015, were community-based, majority were from rural and there were cultural reasons of keeping neonates inside home; but in current study majority of them were from urban and it was conducted among those mothers who came for immunizing their babies.…”
Section: Discussionmentioning
confidence: 54%
“…This is higher than the studies conducted in Tenta District, (41.3%) and Wolkite, (32%), Ambo town (79.2%). 17,24,27 The discrepancy might be because there is better health coverage in the current study area and they are near to the center for careseeking than those studies.…”
Section: Discussionmentioning
confidence: 61%
“…Data was distributed into two further categories, appropriate healthcare-seeking are those mothers who were taken their child to the registered health facilities (government or private health facility) after their baby's developed danger signs and inappropriate healthcare-seeking are those who sought the care other than that. 24…”
Section: Measurement and Definitionsmentioning
confidence: 99%